Missed opportunities for delivering nutrition interventions in first 1000 days of life in India: Insights from the National Family Health Survey, 2006 and 2016 - Nguyen, Phuong Hong; Avula, Rasmi; Tran, Lan Mai; Sethi, Vani; Kumar, Alok; Baswal, Dinesh; Hajeebhoy, Nemat; Ranjan, Alok; Menon, Purnima (BMJ, 2021)
Existing health and community nutrition systems have the potential to deliver many nutrition interventions. However, the coverage of nutrition interventions across the delivery platforms of these systems has not been uniform. We (1) examined the opportunity gaps between delivery platforms and corresponding nutrition interventions through the continuum of care in India between 2006 and 2016 and and (2) assessed inequalities in these opportunity gaps.